Bandos mistos de aves em gradiente floresta-savana no sudoeste do Brasil - Della Flora, Franchesco (2014)
Mixed flocks of birds are subsets of the community in which species interact positively to obtain benefits in predator avoidance and increase foraging efficiency. These interactions may be more or less strengthened depending on the species involved, by spatial and environmental factors that may affect the distribution of species, and according to traits and phylogeny. In this thesis, I verified the richness and composition of avian mixed flocks, as well the partition of Beta diversity and it relation with space (neutral-based processes) and environmental filters (niche-based processes), and which ecological processes drive the functional and phylogenetic structure of mixed flocks in a regional scale in southwestern Brazil. The mean richness per flock showed no variation among the four vegetation types, but the composition was significantly different. Basileuterus culicivorus (leader), Casiornis rufus, Myiarchus tyrannulus and Turdus leucomelas (followers) were the most frequent species in most of phytophysiognomies. According to species compositions and gradients in each vegetation type, we classified the mixed flock species in four main groups: (1) small insectivorous species of heterogeneous flocks; (2) diet generalist species of canopy flocks; (3) open savanna species; and (4) large size species. All types of vegetation present aggregation more than by chance. Non-random pairwise associations presented much more aggregation than segregated: Closed woodland savanna (cerradão) present more number of aggregations than Semideciduous and Riparian forest. Furthermore, leader-leader and leader-follower pairwise associations were less aggregated than followers associations over all habitats, but there was no significant difference to Closed woodland savanna. The spatial turnover was the most important component in the structuring of avian mixed flocks both flock and forest types in multiple-sites. The spatial turnover dissimilarity of understory, heterogeneous, riparian forest and semideciduous flocks was related positively with geographical distance, while dissimilarity of heterogeneous flocks was positively with temperature and precipitation gradient. However, understory flocks showed negative relation with distance classes higher than 400 km suggesting a species similarity according to forest types, and supporting the Niche theory. The observed patterns of beta diversity of avian mixed flocks suggest both neutral and niche-based processes driven by dispersal ability and deterministic filtering of the species across spatial and environmental gradients. Mixed flocks can be structured in different ways according to it phylogenetic and functional diversity. The morphological traits of the participating species were phylogenetically conserved while behavioral were more labile along the phylogeny, or even convergent. Habitat filtering are probably the most important in the organization of mixed flocks in most forest environments, while facilitation is more influential on savannas.